Trajectories of distress regulation during preschool vaccinations: child and caregiver predictors. Issue 3 (5th March 2022) - Shiff, Ilana; Greenberg, Saul; Garfield, Hartley; Pillai Riddell, Rebecca
Abstract : Preneedle distress and parent verbalizations postneedle are differentially associated with trajectories of pain-related distress during preschooler vaccinations. Abstract: Recent research has highlighted the need for a deeper understanding of the heterogeneity in trajectories of children's distress after acute pain exposure, moving beyond the group means of behavioural pain scores at a single timepoint. During preschool vaccinations, 3 distinct trajectories of postvaccination pain regulation have been elucidated, with approximately 75% of children displaying trajectories characterized by downregulation to no distress by 2 minutes postneedle and 25% concerningly failing to downregulate by 2 minutes. The objective of this study was to examine child and caregiver predictors of preschool children's postvaccination regulatory patterns. Our results indicated that higher child baseline distress, more caregiver coping-promoting verbalizations in the first minute after the needle, less coping-promoting verbalizations in the second minute, and more caregiver distress-promoting verbalizations in the second minute after the needle were associated with membership in the trajectories characterized by high distress. Furthermore, although all children's pain-related distress at various timepoints throughout the appointment was most strongly predicted by previous pain scores, different patterns of associations emerged depending on the trajectory exhibited. This research highlights both the need to minimize distress before the needle to avoid the highly distressed trajectory and the importance of considering the heterogeneity of trajectories of preschool pain responding when examining the factors that are associated with children's pain-related distress.